1994
DOI: 10.1507/endocrj.41.437
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide Treatment Results in the Inhibition of GH Gene Expression in the Adenoma of the Patients with Acromegaly.

Abstract: Abstract.Seven patients with growth hormone (GH 3) The amounts of GH mRNA in the adenoma from the octreotide-treated patients were 4.2 ± 1.8 (mean ± SEM; expressed in an arbitrary unit) and were significantly less than those from the non-treated (33.6 ± 9.1). These data suggest that octreotide inhibits not only GH release from the adenoma but also its biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…After 96 h incubation, GH mRNA levels increased in two, and were slightly decreased in one of three adenomas tested. Tsukamoto et al (1994) showed that GH mRNA levels were significantly lower in GH-secreting pituitary adenoma tissue obtained from seven patients treated preoperatively with octreotide than in adenomas derived from 18 non-treated patients.…”
Section: Gh Secretion and Gh Mrna Expressionmentioning
confidence: 91%
See 1 more Smart Citation
“…After 96 h incubation, GH mRNA levels increased in two, and were slightly decreased in one of three adenomas tested. Tsukamoto et al (1994) showed that GH mRNA levels were significantly lower in GH-secreting pituitary adenoma tissue obtained from seven patients treated preoperatively with octreotide than in adenomas derived from 18 non-treated patients.…”
Section: Gh Secretion and Gh Mrna Expressionmentioning
confidence: 91%
“…Studies in pituitary cell cultures from animals (Barinaga et al, 1985;Fukata et al, 1985) have shown that SRIF regulates GH release, but has no effect on basal levels of GH synthesis or gene transcription (for review see Luque et al (2008)). However, other studies have shown a decrease in somatotroph GH mRNA levels (Acunzo et al, 2008;Sugihara et al, 1993;Tsukamoto et al, 1994), maintaining the controversy on this issue. Interestingly, observations in primary pituitary cell cultures from pigs and baboons (Luque et al, 2006) indicate that SRIF may exert biphasic effects on GH release (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While direct inhibition of pituitary hormone transcription has yet to be definitively associated with SRIF signaling, as some studies demonstrate a SRIF-dependent decrease in GH mRNA levels (Sugihara et al 1993, Tsukamoto et al 1994, Acunzo et al 2008) others describe no change (Simard et al 1986, Davis et al 1989, Namba et al 1989, Tanner et al 1990, Gruszka et al 2007, and some even demonstrate upregulation of gene expression possibly reflecting a GH-rebound effect after termination of SRIF treatment; the latter exemplifies the importance of outcome measurement timing. SRIF did not affect GH mRNA expression, but did suppress intracellular GH protein levels and decreased GH secretion in primary rat anterior pituitary cells (Simard et al 1986).…”
Section: Gh Secretionmentioning
confidence: 99%
“…Most older studies (5, 6) did not show SRIF action on GH gene expression. However, more recent studies (7)(8)(9)(10) indicate that SRIF might affect GH gene expression. SRIF also inhibits PRL secretion from human PRLsecreting pituitary adenomas in vitro and PRL-producing cell lines (11,12) with unclear effects on the PRL gene.…”
mentioning
confidence: 99%